Decision Making from the Experience of Orthognathic Surgery Patients: A Grounded Theory Approach. (July 2022) - Paul, N.R.; Baker, S.R.; Gibson, B.J.
Introduction: Patients' decisions to undergo major surgery such as orthognathic treatment are not just about how the decision is made but what influences the decision. Objectives: The primary objective of the study was to identify the key processes involved in patients' experience of decision making for orthognathic treatment. Methods: This study reports some of the findings of a larger grounded theory study. Data were collected through face-to-face interviews of patients who were seen for orthognathic treatment at a teaching hospital in the United Kingdom. Twenty-two participants were recruited (age range 18–66 y), of whom 12 (male = 2, female = 10) were 6 to 8 wk postsurgery, 6 (male = 2, female = 4) were in the decision-making stage, and 4 (male = 0, female = 4) were 1 to 2 y postsurgery. Additional data were also collected from online blogs and forums on jaw surgery. The data analysis stages of grounded theory methodology were undertaken, including open and selective coding. Results: The study identified the central role of dental care professionals (DCPs) in several underlying processes associated with decision making, including legitimating, mediating, scheduling, projecting, and supporting patients' decisions. Six categories were related to key aspects of decision making. These were awareness about their underlying dentofacial problems and treatment options available, the information available about the treatment, the temporality of when surgery would be undertaken, the motivations and expectation of patients, social support, and fear of the surgery, hospitalization, and potentially disliking their new face. Conclusion: The decision-making process for orthognathic treatment is complex, multifactorial, and heavily influenced by the role of DCPs in patient care. Understanding the magnitude of this role will enable DCPs to more clearly participate in improving patients' decision-making process. The findings of this study can inform future quantitative studies. Knowledge Transfer Statement: The results of this study can be used both for informing clinical practice around enabling decision making for orthognathic treatment and also for designing future research. The findings can better inform clinicians about the importance of their role in the patients' decision-making process for orthognathic treatment and the means to improve the patient experience. It is suggested that further research could be conducted to measure some of the key constructs identified within our grounded theory and assess how these change during the treatment process.